Generalized Slope Detection and Ranging turbulence profiling at Las Campanas Observatory. Issue 2 (15th June 2016) - Goodwin, Michael; Jenkins, Charles; Lambert, Andrew
Abstract: We present two models of the optical turbulence profile (model-OTP) for Las Campanas Observatory (LCO) based on measurements conducted during 2007 and 2008 using the Generalized Slope Detection and Ranging (SLODAR) method. The model-OTPs can be used as input into simulations to assess the performance of adaptive optics for the Giant Magellan Telescope. Of particular interest is the strength of the ground-layer turbulence for ground-layer adaptive optics. A total of two 1-week observing data was collected using a purpose-built instrument where observations of a bright double star are imaged by 24 × 24 Shack–Hartmann taken with the LCO 100-inch du Pont telescope. The analysis of the data yielded model-OTP consisting of a handful of statistically prominent thin layers that are statistically separated into the ground layer (below 0.5 km) and the free atmosphere for good (25 per cent), typical (50 per cent) and bad (25 per cent) observing conditions. We demonstrate that using the novel technique of Generalized SLODAR we were able to achieve three times the nominal height resolution of SLODAR and uncover important structural details in the ground layer.